Implementation of a Web-Based Information System in Karang Taruna Parangloe: Implementasi Sistem Informasi Berbasis Web di Karang Taruna Parangloe - Indra, Dolly; Syahnur, Muh. Haerdiansyah; Lilis Nur Hayati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study explores the implementation of a web-based information system for Karang Taruna Parangloe, a youth organization in Kelurahan Lanna, Parangloe District. The initiative was driven by the need to improve information dissemination, which previously relied on traditional methods like WhatsApp groups. While convenient, this approach had limitations in reaching a broader audience and effectively promoting organizational activities. To address these challenges, a Community Partnership Program (PKM) was carried out in four key stages: observation, socialization and training, technology implementation, and evaluation. During the observation phase, it became clear that the organization lacked an official platform for sharing updates and announcements. This was followed by socialization and training sessions, aimed at improving digital literacy among members, equipping them with the skills needed to manage and utilize a web-based system.The technology implementation phase focused on developing and launching the organization's official website, https://karangtarunaparangloe.com. Designed as a comprehensive information hub, the website includes a user guide to help administrators manage content effectively. The evaluation phase showed significant improvements in members' understanding and technical skills, with average post-test scores rising from 62 to 85. More than just a tool for sharing information, the website has helped enhance the organization's image and boost community engagement. This initiative demonstrates the power of digital transformation in empowering youth organizations and strengthening communication within communities. It also serves as an inspiring example for other organizations looking to adopt digital solutions to streamline operations and enhance their outreach efforts.